About the prognostic index of morbidity and mortality due to cardiovascular disease associated with atherogenic risk factors - Jorge Manuel Pérez Milian (Revista Cubana de Medicina Militar)
About the prognostic index of morbidity and mortality due to cardiovascular disease associated with atherogenic risk factors